Orientace na konkurenci u hi-tech podniků - Kaňovská, Lucie; Tomášková, Eva (Vysoké učení technické v Brně, Fakulta podnikatelská, 2012)
Purpose: The purpose of this paper is to examine the connection between market orientation and mainly competitor orientation and business performance at the hi-tech companies in the Czech Republic. Design/methodology/approach: The paper involves the New Method for measuring of market orientation. Data are collected through the survey and were used for the data analysis. Findings: The paper involves new aspects for perceiving competitor orientation, as a part of market orientation, and business performance. The result concurs with the results of researches of market orientation realized at this branch. Results show that competitor orientation has significant influence on business performance. Research limitations implications: The limitations are based on the methodology used for gaining data. However, the overall response rate is almost 20 %. The hi-tech industry is fast changing. From this reason, there can be many changes and it is impossible to repeat the research at the same companies. Practical implications: Our findings can help to understand market orientation and its relationship to competitors and business performance. Managers can use method for measuring of market orientation and can find out the level of market orientation at their companies. They can compare their results with the published average results of hi-tech companies. Originality/value: The originality of the paper comes from combining market orientation, the view of competition and business performance at hi-tech companies. The measurement of market orientation was made through the New Method. The model of the New method was constructed along after analysis of other 25 methods; we tried to eliminate the failings criticized in other methods.
Competitor Orientation at the Hi-tech Companies
Keywords: Market orientation; Competition; Business Perfomance; Hi-tech companies; The Czech Republic